2002
DOI: 10.1200/jco.2002.20.6.1625
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Malignant Transformation in Monoclonal Gammopathy of Undetermined Significance and Smoldering Multiple Myeloma

Abstract: Careful evaluation of marrow plasmacytosis, urinary paraprotein, background immunoglobulins, ESR, and paraprotein isotype might help identify at presentation patients with benign monoclonal gammopathies requiring stricter monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
1
17

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(109 citation statements)
references
References 31 publications
4
87
1
17
Order By: Relevance
“…The role of immunoparesis of the noninvolved isotypes had been addressed before. In MGUS, suppression of the noninvolved polyclonal isotypes was associated with a higher risk for progression into active disease 6, 29, while in smoldering myeloma discrepant findings have been reported. Pérez‐Persona et al 30 identified immunoparesis as a significant risk factor for progression and included this parameter in a risk model for patients with smoldering myeloma 31.…”
Section: Discussionmentioning
confidence: 93%
“…The role of immunoparesis of the noninvolved isotypes had been addressed before. In MGUS, suppression of the noninvolved polyclonal isotypes was associated with a higher risk for progression into active disease 6, 29, while in smoldering myeloma discrepant findings have been reported. Pérez‐Persona et al 30 identified immunoparesis as a significant risk factor for progression and included this parameter in a risk model for patients with smoldering myeloma 31.…”
Section: Discussionmentioning
confidence: 93%
“…Confirmamos que los pacientes con fenotipo evolving presentan un mayor riesgo de progresión a mieloma. Además, estudiamos una serie de biomarcadores que predicen conversión a MM en el MGUS 13,17 . Observamos que dichos marcadores también predicen la aparición de un fenotipo evolving.…”
Section: Discussionunclassified
“…A lo largo del tiempo, se han descrito una serie de factores que al diagnóstico estratifican el riesgo de conversión a MM en el MGUS. Así, un porcentaje elevado de CP en la médula ósea (entre 6 y 9%) o la presencia de CP circulantes (entidades que se ven raramente en el MGUS) se asocian con una mayor probabilidad de progresión 13,14 . La presencia de CP con un fenotipo aberrante también aumenta el riesgo de progresión [14][15][16] .…”
Section: Introductionunclassified
“…The impact of the M-protein size was well-demonstrated in the largest series with longest follow-up reported thus far, in which the risk of MGUS progression at 20 years progressively increased from 14%, 25%, 41%, and 49% for a monoclonal protein higher than 0.5 g/dL, 1.5 g/dL, 2 g/dL, and 2.5 g/dL, respectively [26••]. The prognostic influence of the proportion of BMPCs has been observed in all the three series in which a bone marrow aspirate was performed and examined [7,27,28]. In almost all series, the immunoglobulin A M-protein type was associated with a significantly higher risk of malignant transformation [7,26••,27,29,30].…”
Section: Monoclonal Gammopathy Of Undetermined Significancementioning
confidence: 96%